A novel Self-Compacting Ultra-High Performance Fibre Reinforced Concrete (SCUHPFRC) derived from compounded high-active powders. (15th January 2018) - Song, Qiulei; Yu, Rui; Wang, Xinpeng; Rao, Suduan; Shui, Zhonghe
Highlights: A self-compacting UHPFRC is developed and evaluated in this study. Silica fume and metakaolin are used to design compounded high-active powders. The hydration kinetics of the newly developed SCUHPFRC is studied. The microstructure development of the newly developed SCUHPFRC is studied. The use of compounded high-active powders is a crucial factor for SCUHPFRC. Abstract: This study addresses a novel Self-Compacting Ultra-High Performance Fibre Reinforced Concrete (SCUHPFRC) derived from compounded high-active powders, including experimental study and mechanism analysis. The SCHUPFRC skeleton is designed based on particle densely packing model, and different proportions of silica fume (SF) and metakaolin (MK) are employed to generate compounded high-active powders. Then, the fresh and hardened behaviors of the developed concrete are evaluated and analyzed. The obtained results show that a UHPFRC with self-compacting ability can be produced based on optimized application of powder materials and particle packing model. Moreover, the effect of hybrid use of SF and MK on UHPFRC properties can be attributed to physical and chemical influences. On the one hand, the utilized MK is more efficient than SF in promoting the hydration kinetics of UHPFRC cementitious system. On the other hand, excess amount of MK can enhance the shrinkage and viscosity of UHPFRC mixture, which result in that its microstructure development may be disturbed by shrinkage caused micro-cracks and trapped bubbles. Hence, to develop a SCUHPFRC with advanced properties, the use of appropriate compounded high-active powders is a crucial factor.